Difference in trends in suicide mortality rates by marital status and age groups from 2000 to 2020 in Japan - Tasuku Okui (PLoS ONE, 2026)
This study examined trends in suicide mortality rates by marital status across age groups in Japan, which have not been investigated to date. We utilized the Vital Statistics and Census data of Japan, which cover nationwide suicide mortality and population. Marital status was categorized as married, never-married, widowed, and divorced, while age groups were divided into 20–39 years, 40–64 years, and ≥65 years. Age-standardized mortality rates (ASMRs) of suicide were calculated by sex, marital status, and each age group. Annual percent changes in suicide mortality rates between 2000 and 2020 were also determined by age-adjusted Poisson regression analysis, followed by another regression analysis evaluating interactions between marital status and year effects by age group. Moreover, an age–period–cohort analysis by marital status was conducted to determine birth cohort effects. In this period, a significant declining trend in suicide mortality rate was observed across all marital status groups among persons aged 40–64 years and ≥65 years, whereas significant downward trends were not observed for never-married men aged 20–39 years and widowed and divorced women aged 20–39 years. Additionally, the interaction between never-married persons and year was significantly positive relative to married persons among men aged 20–39 years. Moreover, the rate ratios of ASMRs for widowed and divorced persons relative to those for married persons tended to be higher among younger persons across the study period. The results of the age–period–cohort analysis revealed that mortality risk increased in recently born cohorts, particularly among widowed and divorced persons, for women. Overall, trends in suicide mortality rates by marital status differed according to age group. Additionally, the suicide mortality rate for divorced and widowed persons aged 20–39 years remained particularly high, suggesting a possible need for targeted suicide prevention efforts in this population.